The intellectual crisis in English Catholicism : liberal Catholics, Modernists, and the Vatican in the late nineteenth and early twentieth centuries /: liberal Catholics, Modernists, and the Vatican in the late nineteenth and early twentieth centuries. (2017) - Schoenl, William J, 1941-
No abstract available